Bridging Practice And Policy: Slow Tourism Governance in Urban Indonesia - Warren Milton Iacocca; Yesaya Sandang (Gadjah Mada Journal of Tourism Studies, 2026)
This study examines the governance of slow tourism in Salatiga, a secondary city in Central Java, Indonesia, by analyzing the relationship between formal policy frameworks and community-level tourism practices. While slow tourism has been widely discussed as a sustainable alternative to mass tourism, its governance in small and medium-sized cities, particularly in Southeast Asia, remains underexplored. Adopting a qualitative approach, this study integrates document analysis of the local tourism master plan, semi-structured interviews with government and community stakeholders, and field observations of tourism sites. The findings reveal a significant disjunction between policy and practice. Slow tourism is actively enacted through community-based initiatives emphasizing experiential depth, local engagement, and small-scale development. However, these practices remain weakly institutionalized within formal governance structures. Policy frameworks demonstrate partial alignment with slow tourism principles, particularly in terms of locality and community participation, but lack integration in key areas such as mobility planning, destination branding, and experience-based performance indicators. Governance remains fragmented, with limited coordination across sectors and a continued reliance on visitor volume metrics. This study argues that slow tourism in Salatiga exists more as a social practice than as a policy design. It contributes to the literature by demonstrating how governance gaps, rather than resource limitations, constrain slow tourism development in secondary cities of the Global South.